A method for detecting carbon and sulfur content after metal chromium sample preparation
By refining the sample preparation and sieving the particle size of the metal chromium samples, combined with the detection and calibration methods of infrared carbon sulfur analyzers, the detection error problem caused by excessive particle size in the prior art is solved, and a more stable and accurate carbon sulfur content detection is achieved.
Patent Information
- Application Number
- CN202411988333.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-08
AI Technical Summary
In the existing metal chromium carbon sulfur content detection, the sample particle size is too large, resulting in large detection errors, and the particle size is lacking, which affects the stability and accuracy of the detection results.
The sample preparation and refinement of the metal chromium sample to be tested using a ball mill or a prototype, and then sieved to 40-80 mesh using a stainless steel screen to narrow the particle size range, and the carbon sulfur content is detected by an infrared carbon sulfur analyzer, and calibration is performed using a calibration curve.
It improves the stability and accuracy of metal chromium carbon sulfur content detection, shortens the detection and analysis time, and reduces the impact of sample particle size on the detection results.
Smart Images

Figure BDA0005223094710000081 
Figure BDA0005223094710000082 
Figure BDA0005223094710000083
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of metal detection, and more specifically, the invention relates to a method for detecting carbon and sulfur contents after metal chromium is sampled. Background Art
[0002] Eliminating the influence of impurities and non-metallic elements in metals is extremely important for improving the physical and chemical properties of metals to meet the requirements of metal materials in different fields and promote the development of various fields. The premise of eliminating impurities is to accurately detect and analyze the impurities in the product, and then design the corresponding impurity removal and purification plan based on the test results.
[0003] In the detection and analysis, sampling and sample analysis are two independent steps in the whole analysis process. The theoretical research on sampling error mainly focuses on the sampling of solid substances. The overall physical and chemical properties of the sample, such as the distribution of component content, particle size and uniformity, will directly affect the sampling error. The particle size of the sample depends on the nature of the object to be measured, which is generally 74μm (200 mesh). If you want to measure easily oxidized and reduced components such as FeO or volatile components, it cannot be too fine, generally 104μm (150 mesh) is sufficient.
[0004] Therefore, the requirements for sample particle size in sample analysis are very strict. The size of the sample particle size has a great influence on the analysis results. If the particle size is required to be 200 mesh according to the nature of the sample, the larger the particle size, the easier it is for the error to increase. If a sample that lacks representativeness is used during the analysis process, or the particle size of the sample does not meet the requirements, resulting in incomplete sample decomposition, it is also an important factor causing errors in the determination.
[0005] Too coarse or too fine particles will cause significant changes in the test results. At present, the particle size of the samples used in the detection of carbon and sulfur content in metal chromium is usually above 425μm (40 mesh), and there is no relevant research on the particle size of metal chromium and then refining the particle size for carbon and sulfur content detection. Summary of the invention
[0006] An object of the present invention is to solve at least the above problems and / or disadvantages and to provide at least the advantages which will be described hereinafter.
[0007] In order to achieve these purposes and other advantages according to the present invention, a method for detecting carbon and sulfur content after metal chromium sampling is provided, comprising the following steps:
[0008] Step 1: Use a ball mill or a sample preparation machine to prepare the metal chromium sample to be tested, and the sample preparation method is one of dry ball milling and wet ball milling;
[0009] Step 2: Sieve the prepared metal chromium sample to be tested through a stainless steel sieve for testing;
[0010] Step 3: Weigh pure iron flux, the metal chromium sample to be tested, tin flux, and tungsten flux, and place them all in a ceramic crucible. Use an infrared carbon-sulfur analyzer to detect the carbon and sulfur data of the sieved metal chromium sample to be tested. Use the calibration curve of the infrared carbon-sulfur analyzer to calibrate the carbon and sulfur content of the metal chromium sample to be tested, thereby obtaining the calibrated carbon and sulfur content of the metal chromium sample.
[0011] Preferably, in step 2, the mesh size of the stainless steel sieve is 40 to 80 meshes.
[0012] Preferably, in step 2, the mesh size of the stainless steel sieve is 40 meshes.
[0013] Preferably, in step 2, the mesh size of the stainless steel sieve is 80 meshes.
[0014] Preferably, in step three, the infrared carbon-sulfur analyzer is a HCS-808 high-frequency infrared carbon-sulfur analyzer.
[0015] Preferably, in step three, the mass ratio of pure iron flux, the metal chromium sample to be tested, tin flux and tungsten flux is 3:2:3:15.
[0016] Preferably, in step three, the ceramic crucible is pre-heat treated at 1000° C. for 1 hour and then cooled before use.
[0017] Preferably, in step three, the pure iron flux is selected from iron purity > 99.8%, C < 0.0005%, S < 0.0005%, and particle size < 1.25mm; the tungsten flux is selected from tungsten particles, W ≥ 99.5%, S < 0.0008%, C < 0.0005%, and particle size is 0.4-0.8mm; the tin flux has S < 0.0008%, C < 0.0005%, and particle size is 0.4-0.8mm.
[0018] Preferably, in step three, the carbon content of the metal chromium sample to be tested is 0.087%, and the sulfur content is 0.0053%.
[0019] Preferably, in the step three, when using an infrared carbon-sulfur analyzer to detect the metallic chromium sample to be tested, ensure the supply of oxygen and nitrogen, the first-level air pressure is above 2Mpa, and the second-level gauge air pressure of the pressure reducing valve is adjusted to 0.5MPa; ensure that the gas path is normal, the analysis pressure gauge on the instrument is 0.08MPa, the top oxygen pressure is 0.15Mpa, the top oxygen rotor flowmeter is 2L / min, and the analysis rotor flowmeter is 3.5L / min; the waveforms of carbon and sulfur are stable, the entire curve is in a parallel trend, the difference between the peak and the trough of the entire waveform is less than 0.003, and the initial voltage of carbon and sulfur is between 0.5 and 1.5V.
[0020] In order to further shorten the detection and analysis time of the carbon and sulfur content of the metal chromium to be tested by the HCS-808 high-frequency infrared carbon and sulfur analyzer, before the carbon and sulfur content of the metal chromium to be tested is detected, the pure iron flux, tungsten flux and tin flux are first refined to obtain a mixed flux, and the pure iron flux, tungsten flux and tin flux are pre-mixed, and the particle size of the pure iron flux, tungsten flux and tin flux is refined within a narrower range, and the uniformity of the mixing of the three fluxes and the uniformity of the particle size distribution are improved, the fluxing effect of each flux is improved, the melting time of the metal chromium and the analysis time of the infrared carbon and sulfur analyzer are shortened, and the stability of the carbon and sulfur content detection is improved; wherein, the specific method of refining the pure iron flux, tungsten flux and tin flux to obtain the mixed flux includes:
[0021] S1. Pure iron flux, tin flux and tungsten flux are mixed in a mass ratio of 3:3:15 to obtain a mixed powder; the mixed powder is ball-milled, silicon nitride is used as a grinding ball, the mass ratio of the grinding ball to the mixed powder is 2-4:1, anhydrous ethanol is used as a ball-milling medium, the amount of anhydrous ethanol is 40% of the volume of the ball mill, and the ball mill is evacuated to 5.5×10 -5 Pa, set the ball mill speed to 1200-1600 rpm, and the ball milling time to 3-12 hours; after ball milling, separate the mixed powder and perform vacuum drying at a drying temperature of 100-120°C and a drying time of 30-50 minutes;
[0022] S2. The dried mixed powder is subjected to vacuum sintering, and the vacuum degree is less than 2.1×10 -6 Pa, sintering temperature is 500-800°C, sintering heating rate is 5-10°C / min, holding time is 5-20min; cooling down to room temperature at a cooling rate of 5-10°C to obtain sintered mixed powder;
[0023] S3, dry ball milling the sintered mixed powder, using stainless steel grinding balls, the mass ratio of stainless steel grinding balls to mixed powder is 4:1, and the vacuum degree of ball milling is less than 4.0×10 -6 Pa, ball milling speed is 400-800rpm, ball milling time is 4-6h, and mixed flux is obtained.
[0024] The present invention has at least the following beneficial effects: the data of the metal chromium, carbon and sulfur content measured by the present invention is more stable and accurate, and the analysis speed is fast and the time required is short. The influence of the sample particle size on the corresponding data of the sample detection can be reduced, and the credibility and accuracy of the data can be improved.
[0025] The method for detecting the carbon and sulfur contents of metallic chromium after sample preparation provided by the present invention comprises the following steps: firstly preparing and refining the metallic chromium sample to be tested, and then screening the sample to 40-80 meshes, so as to reduce the particle size of the metallic chromium sample to be tested to a narrower range. The results show that, compared with the metallic chromium sample to be tested which has not been prepared, the carbon and sulfur detection temperature stability of the metallic chromium sample after sample preparation is higher, and the error range of the metallic chromium sample to be tested after sieving with 80 meshes is significantly better than that of the metallic chromium sample to be tested after sieving with 40 meshes, indicating that within the range of 40-80 meshes, the smaller the particle size of the metallic chromium sample to be tested, the higher the stability of carbon and sulfur content detection, and the shorter the detection and analysis time.
[0026] At the same time, the present invention uses a ball milling method to prepare the metal chromium sample to be tested, and the D90 particle size of the metal chromium sample to be tested can be reduced to 46.8 μm after ball milling, further refining the particle size of the metal chromium sample to be tested, and at the same time, the metal chromium sample to be tested obtained by ball milling of the present invention has a further improved carbon and sulfur content detection stability, and the detection and analysis time is also further shortened.
[0027] Other advantages, objectives and features of the present invention will be embodied in part through the following description, and in part will be understood by those skilled in the art through study and practice of the present invention. DETAILED DESCRIPTION
[0028] The present invention is described in further detail below so that those skilled in the art can implement it according to the description.
[0029] It should be understood that the terms such as “having”, “including” and “comprising” used herein do not exclude the existence or addition of one or more other elements or combinations thereof.
[0030] The working conditions of the HCS-808 high-frequency infrared carbon-sulfur analyzer used in each embodiment are:
[0031] Ensure the supply of oxygen and nitrogen, the first-level air pressure is above 2Mpa, and adjust the second-level gauge pressure of the pressure reducing valve to 0.5MPa; ensure that the gas circuit is normal, the analytical pressure gauge on the instrument is 0.08MPa, the top oxygen pressure is 0.15Mpa, the top oxygen rotor flowmeter is 2L / min, and the analytical rotor flowmeter is 3.5L / min; the waveforms of carbon and sulfur are stable, the entire curve is in a parallel trend, the difference between the peak and the trough of the entire waveform is less than 0.003, and the initial voltage of carbon and sulfur should be between 0.5-1.5V.
[0032] The ceramic crucible used in each embodiment needs to be treated at 1000° C. for 1 hour and then cooled before use. The stainless steel sieve used for sieving the sample particle size must be cleaned before and after use.
[0033] Among them, the specific method for calibrating the HCS-808 high-frequency infrared carbon and sulfur analyzer using a standard metal chromium sample in Example 1, Example 2, Example 3 and Example 4 includes:
[0034] Weigh 0.3g of pure iron flux (iron content>99.8%, C<0.0005%, S<0.0005%, particle size<1.25mm), 0.2g of standard metal chromium sample (carbon content of 0.087%, sulfur content of 0.0053%), 0.3g of tin flux, and 1.5g of tungsten flux (S<0.0008%, C<0.0005% in tin particles, particle size of 0.4-0.8mm) in sequence and place them in a ceramic crucible;
[0035] Gently shake the ceramic crucible to evenly distribute and mix the pure iron flux, tin flux, tungsten flux and standard metal chromium sample;
[0036] Place the ceramic crucible on the HCS-808 high-frequency infrared carbon and sulfur analyzer to start analyzing and testing the standard metal chromium sample.
[0037] The calibration curve of the infrared carbon-sulfur analyzer is drawn using the carbon and sulfur contents of the standard metal chromium sample obtained by the test; wherein, in this embodiment, the same standard metal chromium sample is selected for two tests, and the expression of the established carbon content calibration curve is y=kx, and the carbon and sulfur contents are calibrated respectively, with the certified mass output by the HCS-808 high-frequency infrared carbon-sulfur analyzer as x, and the adjusted area output as y, wherein the x and y values of the two tests are shown in the following table:
[0038] x y Standard metal chromium sample 1 0.8751 0.9447 Standard metal chromium sample 2 0.9345 0.9683
[0039] The fitted carbon content calibration curve expression is: y=0..3973x, and the correlation coefficient is 0.3.
[0040] Similarly, the sulfur content is calibrated, and the two data are shown in the following table:
[0041] x y Standard metal chromium sample 1 0.8741 0.9943 Standard metal chromium sample 2 0.7992 0.9104
[0042] The calibration curve expression of sulfur content obtained by fitting is: y=1.1196x, and the correlation coefficient is 0.1.
[0043] Embodiment 1:
[0044] This embodiment provides a method for detecting carbon and sulfur content after preparing a metal chromium sample, comprising the following steps:
[0045] Step 1: using a sample preparation machine to prepare a sample of the metal chromium sample to be tested;
[0046] Step 2: Sieve the prepared metal chromium sample to be tested through a 40-mesh stainless steel sieve for testing;
[0047] Step 3: When measuring the sample, weigh 0.3g of pure iron flux, 0.2g of the metal chromium sample to be measured, 0.3g of tin flux, and 1.5g of tungsten flux, put them all in a ceramic crucible, and mix them evenly; after weighing, use HCS-808 high-frequency infrared carbon-sulfur analyzer to analyze and detect, and use the calibration curve of HCS-808 high-frequency infrared carbon-sulfur analyzer to calibrate the carbon and sulfur content of the metal chromium sample to be measured, so as to obtain the calibrated carbon and sulfur content of the metal chromium sample.
[0048] In this embodiment, the analysis time of the HCS-808 high-frequency infrared carbon-sulfur analyzer for detecting the carbon content is 43 seconds, and when the sulfur content of the metal chromium sample to be tested is detected, the analysis time is 40 seconds.
[0049] Embodiment 2:
[0050] This embodiment provides a method for detecting carbon and sulfur content after metal chromium sampling, comprising the following steps:
[0051] Step 1: using a sample preparation machine to prepare a sample of the metal chromium sample to be tested;
[0052] Step 2: Sieve the prepared metal chromium sample to be tested through a 80-mesh stainless steel sieve for testing;
[0053] Step 3, weigh 0.3g of pure iron flux, weigh 0.2g of the metal chromium sample to be tested, 0.3g of tin flux, and 1.5g of tungsten flux, put them all in a ceramic crucible and mix them evenly; after weighing, use HCS-808 high-frequency infrared carbon-sulfur analyzer to analyze and detect, and use the calibration curve of HCS-808 high-frequency infrared carbon-sulfur analyzer to calibrate the carbon and sulfur content of the metal chromium sample to be tested, so as to obtain the calibrated carbon and sulfur content of the metal chromium sample.
[0054] In this embodiment, the analysis time of the HCS-808 high-frequency infrared carbon-sulfur analyzer for detecting the carbon content is 39 seconds, and when the sulfur content of the metal chromium sample to be tested is detected, the analysis time is 410 seconds.
[0055] Example 3
[0056] This embodiment provides a method for detecting carbon and sulfur content after preparing a metal chromium sample. The difference from Embodiment 1 is that in step 3, 2.1 g of mixed flux is used to replace 0.3 g of pure iron flux, 0.3 g of tin flux, and 1.5 g of tungsten flux. The preparation method of the mixed flux includes:
[0057] S1. Pure iron flux, tin flux and tungsten flux were mixed in a mass ratio of 3:3:15 to obtain a mixed powder; the mixed powder was ball-milled, silicon nitride was used as grinding balls, the mass ratio of grinding balls to mixed powder was 4:1, anhydrous ethanol was used as ball-milling medium, the amount of anhydrous ethanol was 40% of the volume of the ball mill, and the ball mill was evacuated to 5.0×10 -5 Pa, set the ball mill speed to 1500rpm, and the ball milling time to 3h; after ball milling, separate the mixed powder and vacuum dry it, the drying temperature is 120℃, and the drying time is 30min;
[0058] S2: The dried mixed powder is subjected to vacuum sintering with a vacuum degree of 1.7×10 -6 Pa, sintering temperature is 800℃, sintering heating rate is 5℃ / min, holding time is 20min; cooling down to room temperature at a cooling rate of 5℃ to obtain sintered mixed powder;
[0059] S3, dry ball milling the sintered mixed powder, using stainless steel grinding balls, the mass ratio of stainless steel grinding balls to mixed powder is 4:1, and the vacuum degree of ball milling is 2.2×10 -6 Pa, the ball milling speed is 600rpm, the ball milling time is 4h, and the mixed flux is obtained. The particle size of the mixed flux is 0.2-0.6mm, and the particle size and distribution concentration are better than the initial particle size distribution of pure iron flux, tin flux and tungsten flux.
[0060] The methods and process parameters of the remaining steps of this embodiment are the same as those of Embodiment 1.
[0061] In this embodiment, the analysis time of the HCS-808 high-frequency infrared carbon-sulfur analyzer for detecting the carbon content is 28 seconds, and when the sulfur content of the metal chromium sample to be tested is detected, the analysis time is 23 seconds.
[0062] Example 4
[0063] This embodiment provides a method for detecting the carbon and sulfur content of metallic chromium after sample preparation. The difference from Embodiment 2 is that in step three, 2.1 g of mixed flux is used to replace 0.3 g of pure iron flux, 0.3 g of tin flux, and 1.5 g of tungsten flux. The preparation method of the mixed flux is the same as that of Embodiment 3.
[0064] In step 1 of this embodiment, a ball mill is used to prepare the metal chromium sample, and the specific method of sample preparation includes:
[0065] S11, put 10kg of high-purity chromium metal and 50kg of steel balls into the ball mill, the steel balls include 10kg of large steel balls with a diameter of 80mm and 40kg of small steel balls with a diameter of 40mm; the vacuum degree of the ball mill is pumped to 1.2×10 -2Pa, then argon gas was introduced to stabilize the air pressure in the ball mill to 980Pa; during ball milling, the speed of the ball mill was 600rpm, the ball milling time was 3h, and after the ball milling was completed, the metal chromium powder was sieved;
[0066] S12, washing and drying the metal chromium powder after ball milling in step 1, then weighing 5g of the metal chromium powder and putting it into 500mL of deionized water, stirring at a speed of 600rpm, and adding 0.5g of polyacrylic acid dispersant at the same time. After the addition of the polyacrylic acid dispersant, the stirring speed is increased to 1500rpm, and then the temperature is raised to 60°C, the dispersion time is 2h, and then solid-liquid separation is performed, and the dispersed metal chromium powder is obtained after washing and drying;
[0067] S13, wet ball milling 10kg of the metal chromium powder dispersed in step 2, the specific method is: 20kg of anhydrous ethanol as the ball milling medium, 80kg of zirconium oxide as the grinding ball, 0.5kg of KH550 as the coupling agent; the metal chromium powder, anhydrous ethanol, zirconium oxide grinding balls and coupling agent are mixed and added to the ball milling tank, the ball milling speed is 600rpm, the ball milling time is 6h, after the ball milling is completed, separation, washing and drying are obtained to obtain the prepared metal chromium sample. After sieving, the D90 particle size of the metal chromium sample prepared in this embodiment is 46.8μm, the particle size distribution concentration is higher, and the particle size is more uniform.
[0068] In this embodiment, the analysis time of the HCS-808 high-frequency infrared carbon-sulfur analyzer for detecting the carbon content is 26 seconds, and when the sulfur content of the metal chromium sample to be tested is detected, the analysis time is 24 seconds.
[0069] Comparative Example 1
[0070] This comparative example provides a method for detecting the carbon and sulfur content of metallic chromium. Compared with Example 1, the difference is that this comparative example does not prepare the metallic chromium sample to be tested, and the D90 particle size of the metallic chromium sample is 440 μm (larger than the 40 mesh particle size sieved in Example 1). The specific method of step three of this comparative example is the same as that of Example 1.
[0071] In this comparative example, the analysis time of the HCS-808 high-frequency infrared carbon-sulfur analyzer for detecting carbon content is 46 seconds, and the analysis time for detecting sulfur content in the metal chromium sample to be tested is 43 seconds.
[0072] In the above Examples 1 to 4 and Comparative Example 1, two groups of parallel samples were tested for each metal chromium sample to obtain Table 1 and Table 2:
[0073] Table 1 Determination results of carbon and sulfur content in samples of Example 1 and Example 2
[0074]
[0075] Table 2 Determination results of carbon and sulfur content in the metal chromium samples to be tested in Example 3 and Example 4
[0076]
[0077] Table 3 Comparative Example 1 Determination results of carbon and sulfur content in the metal chromium samples to be tested
[0078]
[0079] In Table 1, the maximum difference in carbon and sulfur content of the same metal chromium sample to be tested is 4ppm (0.0004%), the data is stable and meets the error requirements, and in Example 2, the metal chromium sample to be tested is sieved through 80 mesh after sample preparation, and its particle size is smaller than that of the comparative example 1 without sample preparation and sieved through 40 mesh in Example 1. The difference in sulfur content detection in Example 2 is only 1ppm (0.0001%), and the two carbon content detection results are the same, indicating that after Example 2 uses the metal chromium to be tested with a smaller sample preparation particle size for detection, the stability of carbon and sulfur content detection is significantly improved; and in Table 2, the two carbon and sulfur content detection results of Example 3 are the same, and the maximum difference in carbon and chromium content of the metal chromium sample to be tested in Example 4 is 1ppm, which is also within the required allowable range, indicating that after the mixed flux is used, the stability and reliability of carbon and sulfur content detection of the metal chromium sample to be tested are further improved.
[0080] The number of devices and processing scales described here are used to simplify the description of the present invention. Applications, modifications and variations of the present invention will be obvious to those skilled in the art.
[0081] Although the embodiments of the present invention have been disclosed as above, they are not limited to the applications listed in the specification and the implementation modes, and they can be fully applied to various fields suitable for the present invention. For those familiar with the art, additional modifications can be easily implemented. Therefore, without departing from the general concept defined by the claims and the scope of equivalents, the present invention is not limited to the specific details and the examples shown and described herein.
Claims
1. A method for detecting carbon and sulfur content after preparing a metal chromium sample, characterized in that: The following steps are involved: Step 1: Use a ball mill or a sample preparation machine to prepare the metal chromium sample to be tested; Step 2: Sieve the prepared metal chromium sample to be tested through a stainless steel sieve for testing; Step 3: Weigh pure iron flux, the metal chromium sample to be tested, tin flux, and tungsten flux, and place them all in a ceramic crucible. Use an infrared carbon-sulfur analyzer to detect the carbon and sulfur data of the sieved metal chromium sample to be tested. Use the calibration curve of the infrared carbon-sulfur analyzer to calibrate the carbon and sulfur content of the metal chromium sample to be tested, thereby obtaining the calibrated carbon and sulfur content of the metal chromium sample.
2. The method for detecting carbon and sulfur content of metallic chromium after sample preparation according to claim 1, characterized in that: In the step 2, the mesh number of the stainless steel sieve is 40 to 80 meshes.
3. The method for detecting carbon and sulfur content of metallic chromium after sample preparation according to claim 1, characterized in that: In the step 2, the mesh number of the stainless steel sieve is 40 meshes.
4. The method for detecting carbon and sulfur content of metallic chromium after sample preparation according to claim 1, characterized in that: In the step 2, the mesh number of the stainless steel sieve is 80 meshes.
5. The method for detecting carbon and sulfur content of metallic chromium after sample preparation according to claim 1, characterized in that: In the step three, the infrared carbon-sulfur analyzer is a HCS-808 high-frequency infrared carbon-sulfur analyzer.
6. The method for detecting carbon and sulfur content of metallic chromium after sample preparation according to claim 1, characterized in that: In the step three, the mass ratio of pure iron flux, the metal chromium sample to be tested, tin flux and tungsten flux is 3:2:3:
15.
7. The method for detecting carbon and sulfur content of metallic chromium after sample preparation according to claim 1, characterized in that: In the step 3, the ceramic crucible is pre-heat treated at 1000° C. for 1 hour and then cooled before use.
8. The method for detecting carbon and sulfur content of metallic chromium after sample preparation according to claim 1, characterized in that: In the step three, the pure iron flux is selected from iron purity>99.8%, C<0.0005%, S<0.0005%, and particle size<1.25mm; the tungsten flux is selected from tungsten particles, W≥99.5%, S<0.0008%, C<0.0005%, and particle size is 0.4-0.8mm; the tin flux has S<0.0008%, C<0.0005%, and particle size is 0.4-0.8mm.
9. The method for detecting carbon and sulfur content of metallic chromium after sample preparation according to claim 1, characterized in that: In the step 3, the carbon content of the metal chromium sample to be tested is 0.087%, and the sulfur content is 0.0053%.
10. The method for detecting carbon and sulfur content of metallic chromium after sample preparation according to claim 1, characterized in that: In the step three, when using an infrared carbon-sulfur analyzer to detect the metallic chromium sample to be tested, ensure the supply of oxygen and nitrogen, the first-level air pressure is above 2Mpa, and the second-level gauge air pressure of the pressure reducing valve is adjusted to 0.5MPa; ensure that the gas path is normal, the analysis pressure gauge on the instrument is 0.08MPa, the top oxygen pressure is 0.15Mpa, the top oxygen rotor flowmeter is 2L / min, and the analysis rotor flowmeter is 3.5L / min; the waveforms of carbon and sulfur are stable, the entire curve is in a parallel trend, the difference between the peak and the trough of the entire waveform is less than 0.003, and the initial voltage of carbon and sulfur is between 0.5 and 1.5V.